Clear-Cell Carcinoma of the Ovary with Bilateral Breast Metastases - Yehuda Galili; Meghan Lytle; Jonathan Bartolomei; Kataria Amandeep; Nichole Allen; S. J. Carlan; Mario Madruga (Case Reports in Oncological Medicine)
Ovarian clear-cell carcinoma is an uncommon subtype of epithelial ovarian carcinoma. It carries a generally poor prognosis because of its resistance to standard treatment and metastatic spread to vital organs. Metastasis to the breast is rare and bilateral breast metastasis is unreported. A 61-year-old white female with a 5-year status poststandard therapy for stage IC clear-cell ovarian carcinoma presented with widespread metastasis. Tissue analysis revealed ovarian cancer metastasis to the breasts bilaterally. Clinical awareness of this metastatic potential is important when staging and developing a treatment plan for patients with ovarian clear-cell cancer.